A plain of colors.: Children's songbook of the eastern plains of Colombia (The Voz a Vos Bulletin, 2021)
The research-creation project: A colorful plain: Colombian Eastern Plain Child Songbook consists of the intervention by German Alejandro Barragan Ramirez of a repertoire of eight unpublished songs composed by Astrid Carolina Arenas within the Joropo musical system. The harmonic arrangements and accompanying melodies were made considering the melodic lines, and using different forms of re-harmonization worked in the analysis and creation workshops taken in the course of the Master in Colombian Music of the El Bosque University, in Bogota, Colombia. The arranging and interpretative work proposed by the author is based on the concept of children's world, a concept that starts from the consideration that the children's world is fantastic; it is a world without frontiers, where magic and imagination floods everything around it. The musical aspects and the coherent articulation between music and text are reflected in a staging and a sound document, which seeks to enrich the scarce children's songbook of the traditional Colombian-Venezuelan eastern plain popular music, not only highlighting their cultural traditions but emphasizing the content of the texts, seeking to be consistent with children's spirit, with compositions that underline region's values, traditions, myths and legends, flora and fauna.